Could Animal-Assisted Therapy Help to Reduce Coercive Treatment in Psychiatry? - Widmayer, Sonja; Borgwardt, Stefan; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2019)
For psychiatric patients, compulsory admission and coercive measures can constitute distressing and sometimes traumatizing experiences. As a consequence, clinicians aim at minimizing such procedures. At the same time, they need to ensure high levels of safety for patients, staff and the public. In order to prevent compulsory measures and to favor the use of less restrictive alternatives, innovative interventions improving the management of dangerous situations are needed. Animal assisted therapy (AAT) is being applied in a variety of diagnoses and treatment settings, and could have the potential to reduce aggression and psychopathology. Therefore, AAT might be of use in the prevention and early treatment of aggression, and might constitute a promising component of treatment alternatives to forced interventions. To our knowledge, no study evaluating the effect of AAT on compulsory measures in persons with psychiatric diseases has been published up to date. This narrative expert review including a systematic literature search examines the published literature about the use of AAT in psychiatry. Studies report reduced anxiety and aggressiveness as well as positive effects on general wellbeing, self-efficacy, quality of life and mindfulness. Although literature on the applicability of AAT as a component of preventive or de-escalating treatment settings is sparse, beneficial effects of AAT have been reported. Therefore, we encourage examining AAT as a promising new treatment approach to prevent compulsory measures.